Beyond the Spongiform Pattern of Gossypiboma: How a Radiopaque Marker Solved the Mystery of a Retained Sponge - Deepthi Sanagavarapu; Vihar Reddy Mallapu; Vadlapally Karuna; D. Ankamma Rao; Mallikarjuna Reddy Mandapati (Indian Journal of Radiology and Imaging)
Gossypiboma, a retained surgical foreign body, is a rare but serious complication with variable clinical and radiological features, posing diagnostic challenges. This case report describes a 55-year-old female with a history of total abdominal hysterectomy and incisional hernioplasty, presenting with a 6-month history of insidious abdominal pain and a palpable right iliac fossa mass. Initial ultrasound suggested a mesenteric dermoid, but her surgical history raised suspicion of gossypiboma. Computed tomography revealed a nonenhancing hypodense lesion with a curvilinear high-density structure (average attenuation of 1200 HU) within causing streak artifacts, characteristic of a radiopaque surgical sponge marker, confirming the diagnosis. Exploratory laparotomy identified an encapsulated surgical mop with dense adhesions, necessitating adhesiolysis, appendectomy, and ileal resection. The postoperative course was uneventful. This case highlights the importance of considering gossypiboma in patients with prior surgery, even without classic imaging features, and underscores the critical role of radiopaque markers in diagnosis.